Iowa RBA, December 2, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for December 2, 1996. Highlights of the update include sightings of a potential second state record Pinyon Jay, a Red Crossbill, a Gyrfalcon, a White-winged Scoter, and a Varied Thrush. Other notable sightings were of a Pomarine Jaeger, Snowy Owls, a Surf Scoter, a Black-legged Kittiwake, a Glaucous Gull, and Thayer's Gulls. Also included are handwritten notes for the next week's update with sightings of all 3 Scoter species and the return of 3 Trumpeter Swans. Epson - sheet feed/flatbed